Chondrosarcoma of Thyroid Cartilage - Case Report - Muhammad Sohaib Nadeem; Ujala Ali; Adnan Zeb; Muhammad Yousaf Khan (Pakistan Armed Forces Medical Journal, 2024)
Chondrosarcomas of the larynx are rare, mainly arising from cartilages of the larynx, including cricoid cartilage, thyroid cartilage epiglottis, and arytenoid cartilages. These can be misdiagnosed initially as benign malignancy. Historically, the treatment used to be surgery, which usually is total thyroidectomy with a loss of voice forever. No gross improvements in treatment occurred, and surgery was the mainstay of the treatment. Chondrosarcoma from other anatomical regions can very rarely cause thyroid metastasis. Here, we present a case of an elderly male who presented with a multinodular goiter and underwent thyroidectomy. On histopathology, he was diagnosed with grade 2, conventional chondrosarcoma.